Subregion duality, wedge classification and no global symmetries in AdS/CFT - Ning Bao; Yikun Jiang; Joydeep Naskar (Journal of High Energy Physics)
Abstract We study various notions of ‘subregion duality’ in the context of AdS/CFT. We highlight the differences between the ‘background wedge’ and the ‘operator reconstruction wedges,’ providing a resolution to the paradox raised in [1]. Additionally, we elucidate the distinctions between four different ‘operator reconstruction wedges’ and demonstrate how to enhance the proof for the absence of global symmetries in geometrical states in AdS/CFT [2, 3] as an example of these distinctions.